High-Bandwidth Active Impedance Control of the Proprioceptive Actuator Design in Dynamic Compliant Robotics - Simon Hjorth Jessing Lund; Peter Billeschou; Leon Bonde Larsen (Actuators, 2019)
Dynamic compliant robotics is a fast growing field because of its ability to widen the scope of robotics. The reason for this is that compliant mechanisms may ensure safe/compliant interactions between a robot and an external element—for instance, a human operator. Active impedance control may widen the scope even further in relation to passive elements, but it requires high-bandwidth robust torque and active impedance control which induces high-noise issues even if high-end sensors are used. To address these issues, a complete controller design scheme, including Field-Oriented Control (FOC) of a Brushless Direct Current (BLDC) motor, is proposed. In this paper, controller designs for controlling the virtual impedance, motor torque and field are proposed which enables high-bandwidth robust control. Additionally, a novel speed and angle observer is proposed that aims to reduce noise arising in the angle sensor (typically a 12-bit magnetic encoder) and a Kalman/Luenberger based torque observer is proposed that aims to reduce noise arising in the phase current sensors. Through experimental tests, the combination of the controller designs and observers facilitated a closed-loop torque bandwidth of <semantics> 2.6 </semantics> <semantics> k </semantics> <semantics> Hz </semantics> and a noise reduction of <semantics> 13.5 </semantics> dB (in relation to no observers), at a sample rate and Pulse Width Modulation (PWM) frequency of 25 <semantics> k </semantics> <semantics> Hz </semantics> . Additionally, experiments verified a precise and high performing controller scheme both during impacts and at a variety of different virtual compliance characteristics.